Finding cures for the emerging yaws: analysis of Kitab Tib Muzium Terengganu and MSS1292 - Mohd Shafri, Mohd Affendi; Shahdan, Intan Azura; Abdul Halim, Nurul Syahirah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2021)
Yaws is a neglected tropical disease infecting underprivileged population living in tropical and subtropical regions. The disease has persisted in low-developed countries and now emerges in Europe due to increase in travel and economic factors. The threat of yaws is demonstrated by the emergence of antimicrobial resistance strain necessitating the pursuit of new cures. In this study, we used Malay medical manuscripts Kitab Tib Muzium Terengganu and MSS1292 to identify possible treatment for yaws. Malay terms synonymous with puru, are listed and categorised in terms of routes of administration and methods of preparation for the remedies. Comparative analysis using modern scientific database Pubmed was performed to find support for the use of the Malay materia medica. The study identified 17 formulations from the manuscripts for three types of yaws. The most common materials mentioned in the Malay medical manuscripts are terusi (copper sulphate), tempurung (coconut shell) and kunyit (Curcuma longa); belerang/belerang bang (arsenic sulphide), beras (rice), lada/lada sulah (pepper) and tuba tikus (arsenous acid). Comparative analysis found that there were no reports on the use of these materials as yaws treatment which open a huge potential for medical research using manuscript data for the treatment of yaws.